1988
DOI: 10.1007/bf00327368
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar changes after microinjection of antibodies to RNA polymerase I into the nucleus of mammalian cells

Abstract: Abstract. After microinjection of antibodies against RNA polymerase I into the nuclei of cultured rat kangaroo (PtK z ) and rat (RVF-SMC) cells alterations in nucleolar structure and composition were observed . These were detected by electron microscopy and double-label immunofluorescence microscopy using antibodies to proteins representative of the three major components of the nucleolus. The microinjected antibodies produced a progressive loss of the material of the dense fibrillar component (DFC) from the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…(22) We therefore have microinjected polymerase I-antibodies into nuclei of cultured mammalian cells and studied nucleolar alterations by double-label immunofluorescence and electron microscopy. (23) In order to follow the fate of the DFC we have used antibodies against fibrillarin, a protein specifically located in this nucleolar component. (1(;,24,25) The effects are striking (Fig.…”
Section: Selective Inhibition Of Rdna Transcription By Microinjectionmentioning
confidence: 99%
“…(22) We therefore have microinjected polymerase I-antibodies into nuclei of cultured mammalian cells and studied nucleolar alterations by double-label immunofluorescence and electron microscopy. (23) In order to follow the fate of the DFC we have used antibodies against fibrillarin, a protein specifically located in this nucleolar component. (1(;,24,25) The effects are striking (Fig.…”
Section: Selective Inhibition Of Rdna Transcription By Microinjectionmentioning
confidence: 99%
“…Commencement of transcription then triggers refolimation of the nucleolus beginning with the coalescence of preformed 'prenucleolar bodies' around the NOR/fibrillar center which results in the formation of a surrounding dense fibrillar layer (Benavente et al, 1987). Selective inhibition of rRNA transcription by microinjection of antibodies to RNA polymerase I into mitotic or interphasic mammalian cells have clearly shown that ongoing transcription is required for the integration of the dense fibrillar component into the nucleolus (Benavente et al, 1987(Benavente et al, , 1988. Furthermore, these experiments have demonstrated that the dense fibrillar component represents a structure sui generis which exists independent of the transcriptional apparatus (for review see Scheer and Benavente, 1990).…”
Section: B Functional Organization Of the Nucleolusmentioning
confidence: 99%
“…As a component of all small nucleolar ribonucleoprotein particles (snoRNPs), fibrillarin seems to be involved in nearly all major posttranscriptional activities in ribosome synthesis, the first steps of rRNA processing, pre-rRNA modification, and ribosome assembly (Tollervey et al, 1993). Specific inhibition of nucleolar transcription by (1) microinjection of anti-RNA polymerase I antibodies into nuclei (Benavente et al, 1988) or (2) treatment of cells with subtoxic concentrations of HgCl 2 (Chen and von Mikecz, 2000) induce redistribution of fibrillarin from the nucleolus to nucleoplasmic aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…As a component of all small nucleolar ribonucleoprotein particles (snoRNPs), fibrillarin seems to be involved in nearly all major posttranscriptional activities in ribosome synthesis, the first steps of rRNA processing, pre-rRNA modification, and ribosome assembly (Tollervey et al, 1993). Specific inhibition of nucleolar transcription by (1) microinjection of anti-RNA polymerase I antibodies into nuclei (Benavente et al, 1988) or (2) treatment of cells with subtoxic concentrations of HgCl 2 (Chen and von Mikecz, 2000) induce redistribution of fibrillarin from the nucleolus to nucleoplasmic aggregates.It is clear from studies using immunogold electron microscopy (Rivett, 1998), immunochemical procedures (Hü gle et al, 1983), and observation of green fluorescent protein (GFP)-tagged proteasome subunits in living cells (Reits et al, 1997) that proteasomes are present in the cytoplasm and in the nucleoplasm of many different cell types but not within nucleoli. In the present study we describe how the nucleolar autoantigen fibrillarin may be subjected to proteasome-dependent proteolysis, nevertheless.…”
mentioning
confidence: 99%